Talitrus saltator (Montagu, 1808), a species complex (Amphipoda, Senticaudata, Talitroidea, Talitridae) - Lowry, J.k.; Myers, A.a. (Zootaxa, 2019)
The frequently studied amphipod genus Talitrus Latreille, 1802, long thought to be monotypic is shown here to include three species. Two species had already been recognized as distinct species. Talitrus cloquetii Audouin, 1826 and T. platycheles Guérin, 1832, but both had long been reduced to synonymy with T. saltator. All three species are described and figured and a key is provided for their identification. Because of the extensive literature associated with the name Talitrus saltator (sensu lato) we have attempted to assign published records to their appropriate species.